New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera) - Popovici, Ovidiu Alin; Masner, Lubomír; Viciriuc, Mădălina; Pintilioaie, Alexandru; Notton, David G.; Talamas, Elijah (Zootaxa, 2018)
This paper documents what we consider to be expanding distributions in three genera of Platygastroidea: Platyscelio Kieffer (Scelionidae), Aphanomerus Perkins (Platygastridae) and Tetrabaeus Kieffer (Platygastridae). Platyscelio africanus Risbec is the first record of Platyscelio in the Western Hemisphere (French Guiana). Aphanomerus is a new record for the continental Nearctic region (USA, Los Angeles) and Tetrabaeus is a new record for the Palaearctic (Ukraine, Georgia, and South Korea) and Sino-Japanese (Japan) regions. Tetrabaeus also expands its known distribution in the Nearctic (Canada and Mexico).        Scanning electron micrographs and brightfield images are provided to enhance knowledge of the morphology of these genera, and to make them more easily recognized in the future. Tetrabaeus americanus (Brues, 1909) and Aphanomerus rufescens Perkins, 1905 are redescribed.